Removal of Zn(II) and Ag(I) by Staphylococcus epidermidis CECT 4183 and Biosynthesis of ZnO and Ag/AgCl Nanoparticles for Biocidal Applications - Antonio Jesús Muñoz; Celia Martín; Francisco Espínola; Manuel Moya; Encarnación Ruiz (Toxics)
The contamination of natural waters with heavy metals is a global problem. Biosorption is an environmentally friendly and effective technology that offers advantages when metals are present in low concentrations. It also facilitates the recovery and conversion of metals, which are valuable resources. The removal capacity of Ag(I) and Zn(II) ions by Staphylococcus epidermidis CECT 4183 and the ability of its cell extract to synthesize Ag/AgCl and ZnO nanoparticles were investigated. Their biocidal capacity was evaluated. The factors involved were optimized and the mechanisms were studied. The optimal conditions for Ag(I) biosorption were pH 4.5 and a biomass dose of 0.8 g/L. For Zn(II), the biomass dose was 0.2 g/L and pH 4.2. A maximum biosorption capacity (Langmuir model) of 47.43 and 65.08 mg/g, respectively, was obtained. The cell extract promoted the synthesis of Ag/AgCl and ZnO nanoparticles with average sizes below 35 nm. The ZnO nanoparticles exhibited excellent inhibitory properties against planktonic cells of five microbial strains, with MIC values ranging from 62.5 to 250 µg/mL. Their response to biofilms remained between 70% and 100% inhibition at low concentrations (125 µg/mL). The studied bacteria show potential to remove heavy metals and promote the environmentally friendly synthesis of biocidal nanoparticles.